Crayfish Self-Administer Amphetamine in a Spatially Contingent Task - Datta, Udita; van Staaden, Moira; Huber, Robert (Frontiers in Physiology, 2018)
Natural reward is an essential element of any organism’s ability to adapt to environmental variation. Its underlying circuits and mechanisms guide the learning process as they help associate an event, or cue, with the perception of an outcome’s value. More generally, natural reward serves as the fundamental generator of all motivated behavior. Addictive plant alkaloids are able to activate this circuitry in taxa ranging from planaria to humans. With modularly organized nervous systems and confirmed vulnerabilities to human drugs of abuse, crayfish have recently emerged as a compelling model for the study of the addiction cycle, including psychostimulant effects, sensitization, withdrawal, reinstatement, and drug reward in conditioned place preference paradigms. Here we extend this work with the demonstration of a spatially contingent, operant drug self-administration paradigm for amphetamine. When the animal enters a quadrant of the arena with a particular textured substrate, a computer-based control system delivers amphetamine through an indwelling fine-bore cannula. Resulting reward strength, dose-response, and the time course of operant conditioning were assessed. Individuals experiencing the drug contingent on their behavior, displayed enhanced rates of operant responses compared to that of their yoked (non-contingent) counterparts. Application of amphetamine near the suprachiasmatic ganglion elicited stronger and more robust increases in operant responding than did systemic infusions. This work demonstrates automated implementation of a spatially contingent self-administration paradigm in crayfish, which provides a powerful tool to explore comparative perspectives in drug-sensitive reward, the mechanisms of learning underlying the addictive cycle, and phylogenetically conserved vulnerabilities to psychostimulant compounds.